2019
DOI: 10.1101/680819
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The full-length transcriptome of Spartina alterniflora reveals the complexity of high salt tolerance in monocotyledonous halophyte

Abstract: 18 Spartina alterniflora (Spartina) is the only halophyte in the salt marsh. However, the 19 molecular basis of its high salt tolerance remains elusive. In this study, we used 20 PacBio full-length single molecule long-read sequencing and RNA-seq to elucidate 21 the transcriptome dynamics of high salt tolerance in Spartina by salt-gradient 22 Spartina. Overall, this study sheds light on the high salt tolerance mechanisms of 34 monocotyledonous-halophyte and demonstrates the potential of Spartina genes for 35 e… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 88 publications
0
11
0
Order By: Relevance
“…Halophytes can survive better under ambient salinity than glycophytes, which might be attributable to proper modulation of genes that play crucial roles in triggering their salt tolerance mechanisms [ 76 , 144 ]. High-throughput transcriptome sequencing is increasingly being used to understand the responses of plants to abiotic stresses at gene expression level [ 145 ]. Recently, Guo et al [ 146 ] conducted a comparative transcriptome analysis of the model halophyte Puccinellia tenuiflora and several glycophytic Gramineae plants to uncover their underlying molecular responses to excessive salt stress.…”
Section: Potential Of Halophytes As Genetic Resources For the Engineering Of Crops With Improved Salt Tolerancementioning
confidence: 99%
“…Halophytes can survive better under ambient salinity than glycophytes, which might be attributable to proper modulation of genes that play crucial roles in triggering their salt tolerance mechanisms [ 76 , 144 ]. High-throughput transcriptome sequencing is increasingly being used to understand the responses of plants to abiotic stresses at gene expression level [ 145 ]. Recently, Guo et al [ 146 ] conducted a comparative transcriptome analysis of the model halophyte Puccinellia tenuiflora and several glycophytic Gramineae plants to uncover their underlying molecular responses to excessive salt stress.…”
Section: Potential Of Halophytes As Genetic Resources For the Engineering Of Crops With Improved Salt Tolerancementioning
confidence: 99%
“…In this study, transcriptome-wide analysis indicated that APA involves in response to high salt stress (Figures 3-4). High salt stress induces a higher number of differential used APA sites along salt stress gradients (Figure 3a), and ∼42% of APA sites are associated with high salt stress, which is much higher than the prevalence of AS events (∼10%) (Ye et al, 2020). In addition, we found that pathways that are related to ion transport, response to osmotic stress, and respond to salt stress are significantly enriched in high salt stress-associated APA (Figure 3c-d).…”
Section: Discussionmentioning
confidence: 99%
“…The invasive monocotyledonous halophyte - Spartina alterniflora ( Spartina ) is a good model to study high salt tolerance mechanism, as it could tolerant to harsh salinity environment in salt marsh (Bedre et al, 2016; Ye et al, 2020). In this study, we used PacBio SMRT sequencing and poly(A) tag sequencing (PAT-seq) to get insight into how APA responds to high salt stress in Spartina .…”
Section: Introductionmentioning
confidence: 99%
“…Spartina alterniflora maintained a higher K + accumulation under high salt stress via the active gene expression dynamics of SaAKT2, SaKAT2, SaSKOR, and SaNHX2. Moreover, the SaNHX2 showed significant upregulation under high salt stress, further indicating the involvement of SaNHX2 in the K + reservoir of Spartina (Ye et al 2019). In S. virginicus, exclusion of ions from roots and secretion of ions from salt glands helped in the achievement of salt balance (Yamamoto et al 2015).…”
Section: Transcriptomic Analysis Revealed Salt Stress-responsive Genesmentioning
confidence: 91%